Prevalence of latent tuberculosis infection in BCG-vaccinated healthcare workers by using an interferon-gamma release assay and the tuberculin skin test in an intermediate tuberculosis burden country - Hung, Wan-Ting; Lee, Susan Shin-Jung; Sy, Cheng-Len; Wu, Kuang-Sheng; Chen, Jui-Kuang; Tsai, Hung-Chin; Chen, Yao-Shen (Journal of microbiology, immunology and infection, 2015)
The risk of healthcare workers (HCWs) acquiring tuberculosis (TB) infection is high. We determined the prevalence of latent TB infection (LTBI) in HCWs with a high Bacille Calmette-Guérin (BCG) vaccine coverage in an intermediate TB burden country by using an interferon-gamma release assay [QuantiFERON-TB Gold (QFT-G)] and by using the tuberculin skin test (TST). Risk factors associated with a positive test were determined. This prospective cross-sectional study enrolled HCWs from a medical center in Taiwan. Participants were grouped into workers without exposure (Group 1) and workers who self-reported a history of TB exposure (Group 2). All participants completed a questionnaire to collect demographic information and risk factors for acquiring TB. The QFT-G test and the TST were administered and risk factors for a positive test were analyzed. We recruited 193 HCWs [149 (77.2%) female workers] with a mean age of 35.6 years. All were BCG-vaccinated. The prevalence of LTBI was 88.8% (based on the TST) and 14.5% (based on the QFT-G test). There was no difference between HCWs with and without known exposure to TB. Agreement between the tests was poor (i.e., the kappa value was less than 0.05). Multivariable logistic regression showed that only the QFT-G test was associated with age (35 years or greater) (adjusted OR, 2.53; p = 0.03). By using the QFT-G test or TST, this study found a similar prevalence of LTBI in HCWs with and without known exposure to TB. This suggests that in intermediate TB burden countries exposure to TB may occur within the hospital and within the community. Compared to the TST, the QFT-G test was correlated better with age, which is a known risk factor for latent TB infection.